Analisis Sistem Informasi Pencatatan Ibu Hamil Di Kabupaten Jember - Ilham Aditya Aji; Atma Deharja; Sustin Farlinda; Efri Tri Ardianto; Maya Weka Santi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
The maternal mortality rate in East Java has increased over the last two years due to restrictions on antenatal care visits. In 2020 Jember Regency was ranked first in the maternal mortality rate (MMR) in East Java as many as 61 people out of 175.53 per 100,000 live births. The Jember Regency Government in 2017 has implemented an information system for recording pregnant women to suppress MMR in Jember Regency but currently, its use is not maximized because there are still obstacles such as users finding it difficult to use it. The purpose of this study was to analyze the information system for recording pregnant women in Jember Regency. This research is a quantitative study with a cross-sectional approach, this approach is used to see the relationship between one variable and another with the Technology Acceptance Model (TAM) method and the research subject is a midwife who uses information systems. The results of the study show that there is a significant relationship between the usability variable and perceived benefits (sig = 0.001, r = 0.483), privacy and confidentiality variables and perceived benefits (sig = 0.023, r = 0.879), and the perceived benefit variable on user intentions. (sig = 0.001, r = 0.468). The suggestion in this study is that the Health Service should make an SOP that requires users to use an information system for recording pregnant women for services to be more intensive and maximal in their use.